2013
DOI: 10.1039/c3ta13239k
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Bi2S3/WO3 heterojunction films exhibiting enhanced photoelectrochemical performance

Abstract: To improve the photoelectrochemical activity of WO 3 , Bi 2 S 3 /WO 3 heterojunction films were designed by coupling WO 3 films with varying amounts of urchin-like Bi 2 S 3 nanospheres. The WO 3 films were composed of WO 3 nanoprism arrays, which were synthesized using a solvothermal method. After coating a single layer of Bi 2 S 3 on top of the WO 3 film, the resulting Bi 2 S 3 /WO 3 heterojunction film showed enhanced photoelectrochemical activity. At 1.2 V vs. Ag/AgCl, the initial photocurrent density of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 44 publications
2
77
1
Order By: Relevance
“…The modification of WO 3 with metal sulfides like CdS [164] or Bi 2 S 3 [165] resulted in extended visible light response and conventional charge transfer from metal sulfides to WO 3 CB.…”
Section: Coupling With Metal Sulfidesmentioning
confidence: 99%
“…The modification of WO 3 with metal sulfides like CdS [164] or Bi 2 S 3 [165] resulted in extended visible light response and conventional charge transfer from metal sulfides to WO 3 CB.…”
Section: Coupling With Metal Sulfidesmentioning
confidence: 99%
“…6 Generally, the semiconductor that is incorporated as a cocatalyst to construct such a self-established heterojunction should possess good electric conductivity, a suitable energy structure and excellent electrochemical activity. [7][8][9][10][11] As a typical layered metal sulfide, MoS 2 has drawn increasing attention because of its layered structure similar to that of graphene, which is composed of three atom layers stacked together through Van der Waals interactions. 12,13 Such a two-dimensional (2D) layeredcrystal structure provides convenient electron transfer and many active sites for interfacial adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 SEM images (a, b) and XRD pattern (c) of Bi 2 S 3 nanorods and Bi 2 S 3 -AuNPs Electrode characterization and detection feasibility assay It has been reported that the PEC response can be increased when the electrode was irradiated from the backside than the frontside [29]. For increasing the detection sensitivity, we investigated the effect of irradiation direction on the PEC response of Bi 2 S 3 /ITO.…”
Section: Characterization Of Aunps-bi 2 Smentioning
confidence: 99%